Structural optimization and magneto-thermal coupling simulation of limited angle torque motor - Xiufeng Xu; Weixiang Cheng; Xu Zhou; Aiguo Zhou; Jiang Jin; Siyuan An; Xiaofeng Zhang (AIP Advances)
The limited-angle torque motor (LATM) is an electric actuator capable of rotating within a limited angular range and outputting a stable torque. It features a simple structure and high reliability and can be used in precise position or torque control scenarios. To reduce the torque fluctuation within the constant torque range (CTR), the effects of the stator tooth topology and size, PM magnetization direction and size, and sleeve permeability on the torque-angle characteristic of the LATM within the CTR were analyzed through FEM simulation, and the characteristics of the LATM before and after optimization were compared. Furthermore, a magneto-thermal coupling simulation of the steady-state temperature increase and thermal deformation generated by the LATM was conducted to study the effect of temperature on the LATM. The results show that the optimized LATM can output a more stable torque within the CTR and that the rated torque fluctuation rate relative to the torque at the zero position decreases by 3.2%. In addition, the temperature increase and corresponding thermal deformation of the optimized motor at 20 °C decreased by 0.22% and 0.29%, respectively.